Efeito do sombreamento de duas espécies arbóreas na atenuação da radiação ultravioleta e microclima em espaços abertos no Campus da UFMT - Conceição, Everaldo Nonato da (2018)
Solar ultraviolet radiation is important for the biosphere. It acts in the formation and variation of the terrestrial atmosphere, life of plants and human beings. Its excess presents danger to the people´s health, affecting the comfort and physiological wellbeing of the passers-by who travel in open spaces unprotected from solar radiation. For that reason, this study aims at studying the effect of tree shading on the attenuation of microclimatic variables and solar ultraviolet radiation below the canopy of two tree species Mangueira (Mangifera indica L.) and Oiti (Licanea tomentosa (Benth.) Fritsch). This study also aimed at identifying if the Leaf Area Index - LAI, would imply in its variation and intensity, having as analysis object the tree and the seasonality. The specimens were chosen for the reason that they are the most used in the afforestation of Cuiabá in the state of Mato Grosso. This study counted on a methodology of quantitative type based on data of global radiation, air temperature, relative air humidity, solar ultraviolet radiation and radiation index. Three micrometeorological stations were used for the data collection, two of them being placed in the shade of each tree species and one exposed to the sun. The measurements occurred during the four seasons of the year, collecting from 15 to 25 days between 8:00 AM and 5:00 PM. The tree specimens attenuated 90% to 95% solar radiation, air temperature from 2° C to 2,5° C, relative air humidity increased from 2% to 6%, solar radiation UV-B decreased from 95% to 99%. For the analysis of the LAI and the UVIndex, a hierarchical classification of the exhaustive CHAID type and analysis of nonparametric variance were used, in which both were identified according to the seasonality. Thus, it can be concluded that the LAI, the tree and seasonality are factors that influence the variation and intensity of the microclimatic variables and the solar ultraviolet radiation in the shade of these arboreal specimens.